PEMODELAN KINETIKA TUMBUH DAN OPTIMASI KADAR N DAN P UNTUK PENINGKATAN LUTEIN MENGGUNAKAN RESPONSE SURFACE METHODOLOGY (RSM) PADA KULTUR DUNALIELLA SP. SEBAGAI ALTERNATIF SUMBER ANTIOKSIDAN - Daffah, Ikhsanul
Lutein is a group of carotenoid compounds that have various uses for health, especially for maintaining eye health. An alternative source of lutein is required that can produce lutein more quickly, in large quantities, is environmentally friendly and sustainable. Dunaliella sp. is one alternative that is being developed as an alternative source of lutein. However, the lutein content in these microalgae is relatively low to be used as a commercial source of lutein, so it is necessary to carry out an optimization process to increase the lutein yield from Dunaliella sp.. Lutein content in Dunaliella sp. can be increased by providing stress during the cultivation process, such as changing the composition of the source of nitrogen (N) and phosphorus (P) medium used. In this research, N and P concentrations were optimized in the Dunaliella sp. cultivation medium. to increase lutein recovery. The cultivation process was carried out on walne medium with varying levels of N and P in the range of 0.34-2.01mM and 0.05mM-0.28m,M respectively, designed using Central-Composite Design. Biomass growth was measured by measuring the dry weight of the biomass. Consumption of nitrate and phosphate by Dunaliella sp. done by optical density measurement with spectrophotometric method. The lutein extraction process was carried out using the maceration method with acetone as a solvent. Analysis of lutein levels in the extract was carried out using High-Performance Chromatography (HPLC) method. Data of Dunaliella sp. growth and consumption of nitrate and phosphate can be well modeled by the logistic equation. N and P levels were optimized using the Response Surface Methodology (RSM) analysis method. The optimum conditions for producing lutein were at initial concentrations of N and P, respectively 2.01mM and 0.28mM. At this optimum condition, the highest biomass and lutein content were produced with the acquisition of 1.08 ± 0.41 g/L and 54.81 ± 12.32 mg/1,00g respectiv,ely, on the 9th day of cultivation.